Acehnese Students’ Perception of Teacher’s Motivational Teaching Strategy in Teaching English - Fadhillah, Yaumil (Universitas Negeri Semarang, 2022)
In English teaching-learning process, Motivational Teaching Strategy is an offer for the teachers to be applied in the class as a purpose of motivating the students. This study aims at exploring the students’ perception towards the motivational teaching strategy developed by Dornyei (2001) A case study is used as a research methodology. The research subject is the 22 male students of second grade in Darul Qur’an Junior High School, Aceh Besar. The data were obtained through close-ended questionnaire and interview guide. The findings reveal that there are ten crucial motivational teaching strategies applied by the teacher in teaching and learning process therewith the reasons according to the students’ perception. This finding is expected to be the reflective-teaching for all English teachers to maintain, develop, and apply the relevant strategies by fully taking into account students’ perception. As this research is considered an initiatory in the focus of motivational teaching strategies of English teaching and learning particularly in Aceh, the research subject used is still partial and there is a limited time in conducting the research. Accordingly, it is prompted for the subsequent researchers to profoundly carry out the similar research in Aceh.